A Survey on Awareness and Influential Factors Among UTHM Pagoh Students Regarding Virtual Gold Investment Scams - NASRUN, NUR FATEHAH; MOHD RAZALI, SITI NOOR ASYIKIN (Enhanced Knowledge in Sciences and Technology, 2025)
Most students had limited awareness of virtual gold investment scams, making them vulnerable to fraud. Virtual gold investment scams exploit students' lack of knowledge and trust in online platforms, leading to financial losses. This study analyses respondent demographics using descriptive analysis and presented as Power BI dashboard visualization. It identifies differences in awareness of virtual gold investment scams based on demographics (Mann-Whitney U, Kruskal-Wallis H), examines the association between awareness and involvement (Cross-Tabulation, Chi-Square), and explores factors influencing involvement through factor analysis. The target group includes UTHM Pagoh undergraduates from FAST (6 programs), FTK (12 programs), and PPD (7 programs). A survey of 360 respondents revealed a significant difference in the level of awareness based on race but no significant difference based on age, year of study, and faculty. Besides, there is no association between the level of awareness and involvement. Key factors influencing involvement were friends, social media, knowledge, perceived benefits and risks, and trust. This study aims to enhance financial literacy and awareness to prevent such scams.